A Systemic Functional Analysis of English Public Signs: Metafunctions and Communicative Purposes in Urban Linguistic Landscapes - Dwi Meisyitah Ananda; Yosafat Barona Valentino (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
English signs in urban public spaces within the linguistic landscape are not merely directional tools, but rather a reflection of identity contestation, globalization, and complex communicative functions. Through a systemic functional linguistics (SFL) perspective, these signs are understood based on the metafunctions of language. This study examines English signs in public spaces within the urban linguistic landscape through a SFL perspective. Using a qualitative descriptive design, 100 English signs were selected from a larger dataset. The research data, focusing on the functional analysis of these English-language public signs, were analyzed qualitatively and descriptively based on ideational, interpersonal, and textual metafunctions, as well as the communicative purposes of English use. The results show that relational meaning is the most dominant ideational pattern, indicating that English is primarily used to identify locations, facilities, and commercial entities. Interpersonal meaning is dominated by neutral and persuasive functions, while textual meaning often emerges through lexical prominence and theme prominence. These signs primarily function informatively and persuasively, demonstrating that English serves not only as a means of communication but also as a social semiotic resource that regulates public space and constructs commercial meanings. These findings suggest that public signs can be valuable authentic materials in English language learning.